1994
DOI: 10.1002/pen.760340502
|View full text |Cite
|
Sign up to set email alerts
|

Principal features of structural relaxation in glassy polymers. A Review

Abstract: The principal features of models of structural relaxation in the glassy state were reviewed. The concepts of fictive temperature as the structural parameter and nonexponentiality and nonlinearity of structural relaxations were described. Various expressions for the structural relaxation time were presented and compared. One particular model was selected and utilized in a parametric optimization study of structural relaxation. Model predictions were checked against experimental results obtained by volumetric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…More on the TNM model limitations can be found e.g. in [37][38][39][40][41][42], where several attempts for improvement of relaxation phenomenology can also be found. Nevertheless, the TNM model is considered a standard in the field of structural relaxation; thus, all theoretical curves shown in this work were calculated using TNM model without any extensions.…”
Section: Discussionmentioning
confidence: 99%
“…More on the TNM model limitations can be found e.g. in [37][38][39][40][41][42], where several attempts for improvement of relaxation phenomenology can also be found. Nevertheless, the TNM model is considered a standard in the field of structural relaxation; thus, all theoretical curves shown in this work were calculated using TNM model without any extensions.…”
Section: Discussionmentioning
confidence: 99%
“…More references and examples on the TNM model limitations can be found in Refs. [183,184,185,186,187].…”
Section: Limitationsmentioning
confidence: 99%
“…Some reviews of the principal phenomenological models of structural relaxation, such as the one proposed by Narayanaswamy [4] and then by Moynihan et al [5] (the NM model), the Scherer-Hodge (SH) model [7,8] or the Kovacs-Aklonis-Hutchinson-Ramos (KAHR) model [13] are available in literature [1,2,14] and also recent discussions involving this type of models can be found (see for example [15][16][17]). Several works have shown that the NM or SH models fail to reproduce the DSC thermograms measured after different thermal histories using a single set of model parameters [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%